Cardiac Manifestations of Antiphospholipid Syndrome With Focus on Its Primary Form - Kolitz, Tamara; Shiber, Shachaf; Sharabi, Itzhak; Winder, Asher; Zandman-Goddard, Gisele (Frontiers in Immunology, 2019)
Antiphospholipid syndrome (APS) is a multisystem autoimmune disease most commonly associated with recurrent arterial and venous thromboembolism and recurrent fetal loss. Other possible antiphospholipid antibody (aPL)-related clinical manifestations include cardiac involvement. The heart is involved through direct (autoimmune mediated) and indirect (thrombosis) mechanisms. There is an increased cardiovascular mortality in APS; however, the cardiovascular risk is lower in patients with primary APS (PAPS) compared with lupus-related APS. Antiphospholipid syndrome (APS) is a multisystem autoimmune disease most commonly associated with recurrent arterial and venous thromboembolism and recurrent fetal loss. Other possible antiphospholipid antibody (aPL)-related clinical manifestations include cardiac involvement. The heart can be involved through immune mediated and /or thrombotic mechanisms. Mortality due to cardiovascular problems is elevated in APS. However, the cardiovascular risk in patients with primary APS (PAPS) compared with lupus-related APS is yet to be established. Cardiac symptoms of APS include valve abnormalities (thickening and vegetations), coronary artery disease (CAD), myocardial dysfunction, pulmonary hypertension and intracardiac thrombi. Heart valve lesions are the most common cardiac manifestation, observed in approximately one third of PAPS patients and usually do not cause hemodynamic significance. Deposits of immunoglobulins including anticardiolipin (aCL), and of complement components, are commonly observed in affected heart valves from these patients. This suggests that an inflammatory process is initiated by aPL deposition, eventually resulting in the formation of valvular lesion. aPL may have a direct role in the atherosclerotic process via induction of endothelial activation. Multiple traditional and autoimmune-inflammatory risk factors are involved in triggering an expedited atherosclerotic arterial disease evident in APS. It is imperative to increase the efforts in early diagnosis, control of risk factors and close follow-up, in the attempt to minimize cardiovascular risk in APS. Clinicians should bear in mind that a multidisciplinary therapeutic approach is of paramount importance in these patients. This article reviews the cardiac detriments of APS, including treatment recommendations for each cardiac complication.